Determinant Factors of Postpartum Visit Attendance in Surakarta: A Retrospective Study - Puriastuti, Emma Anastya; Hardiningsih, Hardiningsih; Pratiwi, Dyah Krisnawati Satia; Rahmawati, Nur Anisah; Suprobo, Nina Rini (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Women can experience complications and mortality in the postpartum period. Women are also burdened with the long-term consequences of complications after delivery. Access to high-quality care during the postpartum period is essential to improving maternal outcomes, but the number of postpartum visits has not met the standard. This study aims to analyze the determinants of postpartum visit attendance in Surakarta.Method: A retrospective case-control study was conducted using secondary data. The database used in this study was derived from maternal and child health books and data from community health centers. All mothers who had completed the postpartum period (≥42 days postpartum) with the inclusion criteria of having a maternal and child health book and living in Surakarta were involved in this study. Data were analyzed descriptively and statistically. The relationship between the two variables was analyzed using the chi-square test. Multivariate analysis was performed using the logistic regression test. Statistical significance was set at P < 0.05.Result: A total of 179 postpartum mothers' data were successfully collected. Most of them had incomplete postpartum visit data. (75.4%). The number of children and type of delivery were related to the status of the mother's postpartum visit (p ≤ 0.05). Other variables, namely age, occupation, insurance ownership, complications during pregnancy, childbirth or postpartum, education, and place of delivery, were unrelated to the completeness of postpartum visits (p> 0.05). The results of multivariate analysis showed that the type of delivery simultaneously affected the mother's postpartum visit. Mothers who experienced a CS delivery compared to normal delivery had a 0.170 times greater chance of having a complete postpartum visit.